The Prefabricated Interior Design Studio: An Exploration into the History and Sustainability of Interior Prefabrication. - Schneiderman, Deborah; Freihoefer, Kara (International Journal of Art & Design Education, 2013)
This article examines the integration of prefabrication into an interior design studio. A review of the literature revealed that while there is a paucity of categorical research focused on this subject, the subject is historically significant with an abundance of evidence regarding the prefabrication of the interior environment dating back thousands of years. The studio began with a research report, which uncovered a lack of specific topical historical evidence correlating prefabrication with interior design. Next, a series of lectures defined the topic 'Prefabricated Interior Design' and introduced sustainable strategies in prefabrication. Finally, students were instructed to create and assemble three separate prefabricated design studies. At the end of the instructional semester students were questioned about their education, attitudes, and professional objectives toward Prefabricated Interior Design. The survey uncovered that students feel Prefabricated Interior Design is 'unrepresented' in historical content and professional practice. The survey also revealed that students' initial awareness of prefabrication in interior design is weak, however, with the implementation of the topic into a studio-based course their attitudes and perceptions toward prefabrication heightened.